A Novel Mutation in Chronic Granulomatous Disease: Treating the Family, Not Just the Patient - Lutzkanin, Kristen; McKeone, Daniel J.; Greiner, Robert; Andreae, Doerthe Adriana (Frontiers in Pediatrics, 2019)
Chronic Granulomatous Disease (CGD) is caused by genetic defects in the phagocyte NADPH oxidase leading to potentially severe infections with catalase positive micro-organisms. With the innate immune system being affected this disease usually presents before the age of 5 years with infections involving the skin, lung, liver or lymphnodes. Infections with specific catalase positive organisms, especially Burkholderia cepacia, Serratia,Nocardia and Chromobacterium violaceum prompt a workup for CGD in affected patients. In addition, a family history of CGD also warrants testing. The pattern of inheritance of CGD varies across geographic regions of the world and societies, with X-linked inheritance being most prevalent in the United States and Europe. Affected patients require life-long therapy with prophylactic antibiotics, antifungals and possibly interferon-gamma. Hematopoietic Stem Cell Transplantation is the only curative therapy known to date. Identification, diagnosis and management of patients with CGD usually involves a multi-specialty team including Pediatrics, Immunology, Infectious Diseases, Hematology/Oncology and often also Pulmonology and GI/Hepatology. Frequent follow up is paramount for good outcomes; infections have to be recognized and treated promptly and often preemptively. This is challenging for most patients and their families but presents a significant barrier for patients with limited access to care, limited resources or other challenging social situations. This case report describes the difficulties of managing a family with a novel mutation and multiple affected family members in different custody arrangements. It highlights the importance of close contact and communication with the family in deciding on management and treatment options. Educating the family and patient is critical to avoid complications of the disease and allow shared decision making that ultimately leads to better outcomes.